FRANCHISE AGREEMENT UNDER THE LAW OF THE RUSSIAN FEDERATION - Iosifovna Sitdikova, Roza; Anatolievich Petrov, Dmitriy (Revista Gênero e Interdisciplinaridade, 2021)
The franchise agreement in the Russian Federation is the main agreement that formalizes the relationship for organizing a business in the form of franchising. Under a franchise agreement, one party (franchisor) undertakes to provide the other party (user), for a fee, for a period or without specifying a period, the right to use in the user’s business a set of exclusive rights belonging to the franchisor, including the right to a trademark, service mark, as well as rights to other objects of exclusive rights provided for by the agreement, in particular to a commercial designation, a secret of production (know-how). The paper analyzes the content and features of this agreement.